Ta’lîm Mahârah Al-Kitâbah bi Istikhdâm Padlet Lil Mubtadîin - Amir, Aisya (Program Studi Pendidikan bahasa Arab IAIN Langsa, 2024)
In this era, online learning has become an essential part of our lives. The internet, as an educational tool, helps and facilitates students' access to numerous resources. It is especially useful for learning the Arabic language. One of the technological tools available online is Padlet, which is a message board where users can post and store various types of content, including videos, images, websites, GIFs, and text. The purpose of this study is to describe the Padlet program and its application in teaching Arabic writing skills to beginners. This study follows a descriptive analysis methodology, as developed by Mills and Haberman, and includes three main stages: data collection, presentation, and conclusion. The results of this study demonstrate that Padlet not only helps students acquire beginner writing skills but also aids in the development of their writing proficiency and boosts their confidence by providing an interactive and supportive environment with detailed examples of various activities. Students can freely share their ideas, receive instant feedback from teachers and peers, and learn by observing others' work.Teaching methods, Writing skills, Padlet programme